Pengaruh Rasio Solvabilitas Terhadap Profitabilitas: (Studi Pada PT. Bukit Asam Tbk) - Lestari, Suprihatin; Kurniasih, Endah Tri; Wiarta, Iqra; Dani, Rian (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the effect of solvency ratios on profitability in mining companies in Indonesia, namely PT. Bukit Asam Tbk which is a state-owned company engaged in the mining industry. The solvency ratios used are debt to Equity Ratio (X1) and Debt to Asset Ratio (X2) while the profitability ratio used is return on assets (Y). The research method used is quantitative descriptive analysis with multiple linear regression as an analysis tool. The data used comes from the company's annual report for the period 2014 - 2023. The research results show a significant influence of the solvency ratio on the profitability ratio.